Kehittämisen palat, yhteisöjen salat näkökulmia koulutukseen ja kasvatukseen - Korhonen, Vesa; Kulju, Pirjo; Annala, Johanna (Tampere University Press, 2017)
This compilation approaches educational and educational communities on an exploratory and developing occasion. In times of individuality, efficiency and competitiveness, countermeasures are needed to build community-building practices. Collaboration requires a common language, common understanding, trust and increasingly multilingualism whose importance has been emphasized with new media and virtual communities. When educating and teaching communities understand the importance of the community, through everyday interaction, there are opportunities to establish strong links between the teacher and the learners. If a common curriculum activity is to be developed as a meaningful negotiation of the entire education and teaching community, it also requires interaction and co-operation between different actors.